Interrogating Native-Speakerism and Linguistic Imperialism in ELT - Anwar, Md.; Ahad, Md.; Karim, Jonaydul (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2025)
This study interrogates the persistent ideologies of native-speakerism and linguistic imperialism in English Language Teaching (ELT), examining how they are reproduced through material production, accent hierarchies, and assessment practices. Extending the conceptual frameworks of Holliday (2006) and Modiano (2001), the research integrates a comparative literature review with empirical qualitative investigation involving 25 ELT professionals and learners from Bangladesh, Brazil, Japan, the United Kingdom, and India. Drawing on semi-structured interviews and focus groups, the study employs thematic and critical discourse analysis to uncover how institutional policies, market forces, and internalized linguistic hierarchies reinforce the privileging of “inner-circle” norms. Findings reveal three interrelated dynamics: (1) institutional and economic constraints sustain Western material dominance; (2) learners and educators internalize accent hierarchies that equate legitimacy with proximity to native norms; and (3) teachers engage in innovative resistance strategies, such as “rubric hacking”, to challenge systemic inequalities. The study contributes to applied linguistics by bridging conceptual debates with empirical evidence, illustrating how native-speakerism operates across contexts and how educators enact localized decolonial practices. Recommendations are proposed for integrating Global Englishes and accent-equity pedagogy into ELT policy, teacher education, and assessment reform.